The Communist Party of the Soviet Union A Functional Analysis - Gehlen, Michael (Indiana University Press, 1969)
The Communist Party of the Soviet Union: A Functional Analysis has a dual function. It is an extensively documented study of the way that economic needs and technological development are forcing political adaptations within the Soviet system; and it is an experimental application of the methods of functional analysis to a dominant political party.